'Observing' unrelaxed clusters in dark matter simulations. Issue 1 (25th September 2019) - Roberts, Ian D; Parker, Laura C
ABSTRACT: We present a detailed study of relaxed and unrelaxed galaxy clusters in a large dark matter only simulation. Recent work has demonstrated clear differences between the galaxy populations in clusters that have Gaussian velocity distributions (relaxed) compared to those that do not (unrelaxed). To directly compare with observations, we identify unrelaxed clusters in the simulations using one-dimensional velocity distributions. We show that non-Gaussian clusters have had recent major mergers and enhanced rates of galaxy infall relative to systems with Gaussian velocity profiles. Furthermore, we find that the fraction of non-Gaussian clusters increases strongly with cluster mass and modestly with redshift. For comparison, we also make use of three-dimensional information available in the simulations to explore the impact of projection on observational measurements. Differences between Gaussian and non-Gaussian clusters are much stronger when three-dimensional information is considered, which demonstrates that the strength of oberserved trends with cluster dynamics are diluted because observed velocity information is limited to one line-of-sight.